Effect of Coenzyme Q10 in Inhibiting Retinal Ganglion Cell Apoptosis on Glaucomatous neuro degeneration Model: Doi: 10.36351/pjo.v41i1.1907 - Putra Iqra, Haikal Hamas; Feryyana, Vella Febri; Roxanne, Joanne; Mudjahidah, Nabillah Hanun; Triningrat, Anak Agung Mas Putrawati (Pakistan Journal of Ophthalmology, 2025)
This study aimed to explore CoQ10 properties in inhibiting retinal ganglion cell (RGC) apoptosis in the glaucomatous animal model.A comprehensive literature search was performed in Medline/Pubmed, Science Direct, ProQuest, and Web of Science till August 8th, 2023. The authors conducted study selection, data extraction, and risk of bias assessment independently. This study was registered at PROSPERO (registration number CRD42023454777).A total of 5 studies which vary in glaucomatous animal models were selected. All the studies showed a decreased mean of apoptotic RGCs in the glaucomatous CoQ10-supplemented model compared to control. Studies suggest CoQ10 may modify Bax/Bad/BcL-xL-mediated apoptotic pathway.Oxidative stress was also shown to be decreased in several studies which was marked by reducing protective oxidative stress markers (SOD2; HO1).Further research on human subjects was needed to explore CoQ10 potentials.